اختبار التكامل المشترك وسببية تودا ياماموتو بين النمو الفلاحي والنمو الاقتصادي في الجزائر خلال الفترة ) 1970 – 2020 ): Cointegration test and Toda Yamamoto causality between agricultural growth and economic growth in Algeria during the period (1970 - 2020) - مولاي علي هواري,; تسابت عبد الرحمان, (Journal of North African Economies, 2025)
The study seeks to determine the impact of agricultural growth on Algeria's economic growth. To do so, we used the Autoregressive Distributed Lag (ARDL) model to test the cointegration and error correction model. This is for Algerian annual data from 1970 to 2020. The findings of the estimation revealed that agricultural growth has positive impact on the GDP per capita growth in the long run, with an elasticity of 0,12. With the exception of the capital variable, which had a negative sign, all of the other variables had positive signs. The greatest effect comes from the labor which has an elasticity of 1,03, followed by export growth, which has an elasticity of 0,27, and finally inflation, which has an elasticity of 0,01. We also put Toda and Yamamoto's (1995) causality approach to the test, finding that there is no causal relationship in both directions between agricultural growth and GDP per capita growth in Algeria.